Micron cage anchored carbon nanotube modified two-dimensional titanium carbide multistage composite material as well as preparation method and application thereof
By introducing the Co3O4-CNT composite material with a micron cage structure on the surface of the two-dimensional MXene-Ti3C2Tx material, the problem of material heavy accumulation is solved and its electrochemical performance is significantly improved.
Patent Information
- Application Number
- CN202411543809.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
AI Technical Summary
Two-dimensional MXene-Ti3C2Tx materials often face heavy stacking problems in practical applications, resulting in the inability to fully exert their electrochemical properties.
By introducing the Co3O4-CNT composite material with a micron cage structure on the surface of the two-dimensional MXene-Ti3C2Tx material, the heavy stacking phenomenon is reduced and the electrochemical performance is improved.
It effectively reduces the heavy stacking effect of the two-dimensional MXene-Ti3C2Tx material and significantly improves its electrochemical performance, including specific capacitance and cycle stability.
Smart Images

Figure CN119340118A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials and electrochemical energy storage materials, and particularly relates to a two-dimensional titanium carbide multi-level composite material modified by micron cage anchored carbon nanotubes, and a preparation method and application thereof. Background Art
[0002] Transition metal oxides (TMOs) are promising pseudocapacitive materials due to their low electronegativity and high electrochemical activity. They are also widely used in supercapacitors, photoelectrocatalysis, batteries, and sensors. Transition metal oxides, especially Co3O4, have twice the capacity of graphite, the most common intercalation electrode material, when used as electrode materials. However, since cobalt is toxic and expensive, and has low electronic conductivity, researchers have tried to replace Co3O4 with cheaper and more environmentally friendly materials. In recent years, carbon materials have been widely used in negative electrode materials for lithium-ion capacitors due to their good conductivity, stability, and low cost. At present, the research on carbon materials mainly focuses on improving their specific surface area, optimizing pore structure, and enhancing interaction with electrolytes. One-dimensional carbon nanotubes (CNTs) have relatively regular pore structures, large specific surface area, high conductivity, and chemical stability. In addition, the researchers also modified the carbon material by doping, coating and other means to improve its electrochemical properties. Co3O4-CNT has excellent conductivity and electrochemical activity, which makes it an ideal electrode material, far exceeding single nickel oxide or cobalt oxide.
[0003] As a new type of two-dimensional material, two-dimensional nano-titanium carbide has broad application prospects in the field of energy storage and conversion. During the etching process, the surface groups of MXene materials are usually composed of F, OH or O, which are called M n+1 X n T x , where T represents the surface group. x ) has a unique two-dimensional layered structure, a large specific surface area and capacity stability, and has good application potential in electrochemical energy storage. It is a potential supercapacitor electrode material. However, in practical applications, MXene-Ti3C2T x The problem of heavy stacking often occurs, which seriously limits its electrochemical performance. The heavy stacking phenomenon refers to the stacking of two-dimensional titanium carbide nanosheets due to interactions such as van der Waals forces and hydrogen bonds during the preparation or use of the nanosheets, thereby forming a three-dimensional structure. This structural change not only reduces the specific surface area of the material, but also affects the transmission efficiency of ions in the material, thereby limiting the application performance of two-dimensional titanium carbide and causing MXene-Ti3C2T xThe theoretical specific capacity of MXene-Ti3C2T is relatively small. x In order to achieve practical application value, it is necessary to adopt some other electrode materials with high theoretical capacity to replace Ti3C2T x Make modification. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the object of the present invention is to provide a micro-cage anchored carbon nanotube modified two-dimensional titanium carbide multi-level composite material and its preparation method and application, by using a high theoretical capacity electrode material to x Modification was carried out by introducing micro cage Mof anchoring carbon nanotube materials on two-dimensional nano titanium carbide to reduce its heavy accumulation, improve and enhance MXene- Ti3C2T x electrochemical performance.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The first object of the present invention is to provide a two-dimensional titanium carbide multi-level composite material modified by micro-cage anchored carbon nanotubes, wherein the composite material is composed of Co3O4-CNT loaded on Ti3C2T x On the surface, Co3O4 is a hollow dodecahedral microcage structure, CNTs are attached to the outer surface of the hollow dodecahedral Co3O4 microcage structure, and CNTs are anchored by Co3O4 on the outer surface of the microcage.
[0006] The second object of the present invention is to provide a method for preparing a two-dimensional titanium carbide multi-level composite material modified by micro-cage anchored carbon nanotubes, which specifically comprises the following steps: Step 1, dissolving zinc nitrate hexahydrate and 2-methylimidazole in methanol, heating and keeping the mixture warm, stirring, separating and drying solid particles generated by the reaction, and obtaining ZIF-8 precursor particles; Step 2, dissolving cobalt nitrate hexahydrate and 2-methylimidazole in methanol to form a mixed solution, then adding the ZIF-8 precursor particles prepared in step 1 to the mixed solution, heating and heat preservation, stirring, separating and drying the solid particles generated by the reaction, and obtaining ZIF-67 coated ZIF-8 (ZIF-8@ZIF-67) precursor particles; Step 3, taking ZIF-8@ZIF-67 precursor particles, calcining to volatilize the zinc element in the inner layer ZIF-8 and grow carbon nanotubes on the surface of the outer layer ZIF-67, then acid washing to remove the Co element not wrapped in the carbon nanotubes, washing and drying, and then oxidizing to obtain Co3O4 micron cage anchored carbon nanotube (Co3O4-CNT) monomer material; Step 4: Take Co3O4-CNT monomer material and Ti3C2T xThe nano powder colloidal suspension is mixed in deionized water to form a colloid and stirred, and then freeze-dried to obtain the Co3O4 micro cage anchored carbon nanotube modified two-dimensional nano titanium carbide (Ti3C2T x @Co3O4-CNT) composite material.
[0007] The present invention prepares a high theoretical capacity MOF material Co3O4-CNT monomer by in-situ generation of a carbon shell, and then uses Co3O4-CNT to synthesize a two-dimensional MXene-Ti3C2T x Surface modification was performed to enhance the two-dimensional MXene-Ti3C2T by utilizing the unique structural advantages of Co3O4-CNT. x Performance of negative electrode, reducing two-dimensional MXene-Ti3C2T x By heavy stacking, a carbon composite negative electrode material with high coating efficiency was prepared.
[0008] Furthermore, in step 1, the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is (5.7~5.9): (6.3~6.5); the reaction system is heated to 55~65°C and stirred for 22~26h.
[0009] Further, in step 2, the mass ratio of cobalt nitrate hexahydrate, 2-methylimidazole and ZIF-8 precursor particles is (5.7-5.9): (6.0-6.2): (0.25-0.75); Furthermore, in step 2, the reaction system is heated to 55-65° C. and stirred for 22-26 hours.
[0010] Furthermore, in step 3, the ZIF-8@ZIF-67 precursor particles are placed in a protective atmosphere for calcination, and are heated to 750~850°C at a heating rate of 2~4°C / min and calcined for 2.5~3.5 h.
[0011] Furthermore, step 3 is carried out in an air atmosphere by heating to 300-400°C for oxidation at a heating rate of 2-4°C / min and keeping the temperature for 3.5-4.5 h.
[0012] Furthermore, in step 4, the Co3O4-CNT monomer material, Ti3C2T x The dosage ratio of nanopowder colloid and deionized water is (80~160) g: 25 L: 30 L.
[0013] Furthermore, in step 4, Ti3C2T x The concentration of nano powder colloid is 1.6 g / L.
[0014] The third object of the present invention is to provide a two-dimensional titanium carbide multi-level composite material modified by the above-mentioned micro-cage-anchored carbon nanotubes as an application of an electrode material.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention utilizes the unique advantages of MOF-based materials ZIF-8 and ZIF-67, such as huge surface area, rich pore structure, adjustable chemical composition and controllable functionality, selects ZIF-67 as a template for carbon nanotube cages, and uses the principle of metal cobalt catalytic growth of carbon nanotubes to prepare a micron cage anchored carbon nanotube (Co3O4-CNT) for modifying two-dimensional MXene-Ti3C2T x , Ti3C2T x @ Co3O4-CNT composite negative electrode material, by using Co3O4-CNT to two-dimensional MXene-Ti3C2T x Surface modification was performed to effectively reduce the two-dimensional MXene-Ti3C2T x The heavy stacking effect improves and enhances the performance of MXene-Ti3C2T x The electrochemical performance of 2D MXene-Ti3C2T x Compared with electrochemical performance, it is significantly improved.
[0016] Traditional MXene-Ti3C2T x The specific capacitance in KOH electrolyte is 377.64 F / g. x @The specific capacitance of the Co3O4-CNT composite material is 974 F / g. Under the condition of current density of 0.5 A / g, the maximum capacitance of the Co3O4-CNT monomer material prepared by the present invention reaches 749 F / g. x @Co3O4-CNT composite material exhibits excellent stability. Under the condition of current density of 2A / g, the capacity is still 89% of the original capacity after 3000 cycles of constant current charge and discharge. After 3000 cycles at a current density of 2 A / g, the capacitor can maintain 92% of the initial capacitance, achieving a good modification effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope photo of the product of Example 3 of the present invention, where a and b are Co3O4-CNT monomer materials, and c is the two-dimensional MXene-Ti3C2T to be modified. x , d is Ti3C2T x @Co3O4-CNT composites; Figure 2TEM image of Example 3 of the present invention, where a is the two-dimensional MXene-Ti3C2T to be modified x , b, c, e are Co3O4-CNT monomer materials, d is Ti3C2T x @Co3O4-CNT composites; Figure 3 The XRD spectra of Examples 1-5 of the present invention, wherein (a) is the XRD spectra of Ti3C2T prepared in Examples 1-5. x @XRD spectrum of Co3O4-CNT composite material, (b) Co3O4-CNT monomer material and Ti3C2T prepared in Example 3 x @XRD spectrum of Co3O4-CNT composite material; Figure 4 Ti3C2T prepared in Example 3 of the present invention x @Co3O4-CNT composite material spectrum, where a is the full spectrum, b is the C1s spectrum, c is the Co2p spectrum, d is the N1s spectrum, e is the O1s spectrum, and f is the Ti2p spectrum; Figure 5 The CV graphs of the product of Example 3 of the present invention at different scanning rates, where (a) is Co3O4 monomer material, (b) is Ti3C2T x @Co3O4-CNT composites; Figure 6 The GCD diagrams of the product of Example 3 of the present invention at different current densities, where (a) is Co3O4 monomer material, (b) is Ti3C2T x @Co3O4-CNT composites; Figure 7 Ti3C2T prepared in Example 3 of the present invention x @The cycling performance of Co3O4-CNT composite material at a current density of 2A / g; Figure 8 CV graphs of the lithium ion capacitor assembled in Example 3 of the present invention at different scan rates; Fig. 9 is a GCD diagram of the assembled lithium ion capacitor of Example 3 of the present invention; Fig.10 This is an EIS graph of the lithium ion capacitor assembled in Example 3 of the present invention; Fig.11 This is a test diagram of the cycle performance of the lithium ion capacitor assembled in Example 3 of the present invention at a current density of 2A / g. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0020] The present invention is further described in detail below in conjunction with the accompanying drawings: Preparation of two-dimensional layered Ti3C2T x Nanopowders and colloids: (1) Preparation of ternary Ti3AlC2 ceramic powder; Preparation of ternary layered Ti3AlC2 ceramic powder according to the method of patent ZL201310497696.9: 1) Mixing the three raw materials according to a molar ratio of Ti: Al: TiC = 1.0: 1.2: 2.0; secondly, placing the three raw materials in a ball mill, using zirconium oxide balls as grinding media, anhydrous ethanol as a ball milling aid, the ball mill speed is 350 rpm, and the mass ratio of balls: material: ethanol = 3.0: 1.0: 1.0, ordinary ball milling for 2 h to obtain a uniform powder, and drying it in a constant temperature drying oven at 40°C; 2) The dried mixture is placed in a corundum crucible, and is heated to 1350°C at a heating rate of 8°C / min by vacuum pressureless sintering, and kept at this temperature for 1 hour, and then cooled to room temperature with the furnace to obtain high-purity Ti3AlC2 ceramic powder; 3) The Ti3AlC2 ceramic powder was subjected to wet high-energy ball milling for 2 h, once every 30 minutes, at a rotation speed of 300 r / min, with a mass ratio of steel balls to ceramic powder of 10:1, and the ground powder was sieved to obtain Ti3AlC2 ceramic powder with a particle size of less than 38 μm.
[0021] (2) Preparation of two-dimensional layered Ti3C2 nanomaterials and their colloids; Preparation of two-dimensional layered Ti3C2T according to the method of patent 201410812056.7 x Nanomaterials: 1) Take 5 g of the Ti3AlC2 ceramic powder obtained in step (1) and slowly immerse it in 80 mL of 40 wt% hydrofluoric acid solution. After no bubbles are generated, stir it magnetically at room temperature for 24 h at a speed of 4500 r / min. Wash the corrosion product with deionized water by centrifugation for about 10 times until the pH value of the supernatant is about 6. Centrifuge it with anhydrous ethanol for 3 times. Finally, dry the black precipitate in vacuum at 40°C for 24 h to obtain a two-dimensional layered Ti3C2T x Nano powder; 2) 0.16g of Ti3C2T x The nanopowder was added to 10 mL of deionized water and diluted to 100 mL with deionized water, i.e., 40 mg of Ti3C2T was contained in every 25 mL. x The nano powder colloidal suspension is ready for use.
[0022] Example 1 Step 1: Microcage-anchored carbon nanotube-modified two-dimensional titanium carbide hierarchical composite (Ti3C2T x Preparation of @Co3O4-CNT): (1) Synthesis of ZIF-8@ZIF-67 precursor particles: 1) To prepare ZIF-8 particles, 5.8 g of zinc nitrate hexahydrate and 6.4 g of 2-methylimidazole were weighed and dissolved in 150 mL of methanol. The mixture was then stirred at 60°C for 24 hours. After the reaction, the solid particles were separated from the solution by centrifugation and dried. After the above steps, ZIF-8 particles were obtained.
[0023] 2) Prepare ZIF-8@ZIF-67 precursor particles. Weigh 5.82 g of cobalt nitrate hexahydrate and 6.16 g of 2-methylimidazole, respectively, and dissolve them in 100 mL of methanol. Add 0.25 g of the prepared ZIF-8 particles to the solution. Then, stir the mixture at 60°C for 24 hours. After the reaction, separate the generated solid particles by centrifugation and dry them to obtain ZIF-8@ZIF-67 precursor particles.
[0024] (2) Synthesis of Co3O4-CNT: 0.5 g ZIF-8@ZIF-67 precursor was heated to 750 °C in an argon atmosphere at a heating rate of 2 °C / min and kept at this temperature for 3 h, so that the zinc element was completely volatilized; a black solid powder was obtained, which was acid-washed in 0.5 M sulfuric acid for 12 h to completely oxidize the Co element not wrapped in the carbon nanotubes, then centrifuged and washed with deionized water, and dried at 60 °C. The dried powder was heated to 300 °C in an air atmosphere in a tube furnace at a heating rate of 2 °C / min for oxidation and kept at this temperature for 4 h to obtain the microcage-anchored carbon nanotube Co3O4-CNT monomer material.
[0025] (3) Synthesis of Ti3C2T x @Co3O4-CNT composite material: Using MOF derivative Co3O4-CNT monomer material and Ti3C2T x Simply mix and stir. First, take 80 mg Co3O4-CNT and disperse it in 30 mL deionized water. Then slowly add 25 mL of a small layer containing 40 mg Ti3C2T x The colloidal solution was stirred for 30 minutes. Then it was transferred to a vacuum freeze dryer and dried at 1 Pa atmospheric pressure and -45 °C for 48 h to obtain a composite material Ti3C2T with a layer of micro-cage-anchored carbon nanotubes on the surface of the flake titanium carbide. x @Co3O4-CNT.
[0026] Step 2, Ti3C2T x Preparation of @Co3O4-CNT electrode: Making electrode sheets from powdered materials: 80% by weight of active material, 10% by weight of conductive carbon black, and 10% by weight of PVDF binder were mixed with an appropriate amount of N-methylpyrrolidone (NMP), coated on copper foil, dried overnight in vacuum at 80 °C, and then cut into discs with a diameter of 1.6 cm to keep the loading capacity of active material at 1 mg / cm 2 , the electrolyte was 1.0 M LiPF6 as solution. The lithium ion capacitor LIC (<0.01 ppm oxygen and water) was assembled in an argon-filled glove box, AC was used as the positive electrode, glass fiber Whatman GF / D was used as the separator, and 1.0 M LiPF6 electrolyte was dissolved in ethylene carbonate (EC): diethyl carbonate (DEC) = 1:1 Vol%.
[0027] Example 2 Step 1, Ti3C2T x Preparation of @Co3O4-CNT: (1) Synthesis of ZIF-8@ZIF-67 precursor particles: 1) Preparation of ZIF-8 particles: Weigh 5.8 g of zinc nitrate hexahydrate and 6.4 g of 2-methylimidazole respectively and dissolve them in 150 mL of methanol. Then, stir the mixture at 60°C for 24 hours. After the reaction, separate the generated solid particles from the solution by centrifugation and dry them. After the above steps, ZIF-8 particles can be obtained.
[0028] 2) Preparation of ZIF-8@ZIF-67 precursor particles: 5.82 g of cobalt nitrate hexahydrate and 6.16 g of 2-methylimidazole were weighed separately and dissolved in 100 mL of methanol. 0.5 g of the prepared ZIF-8 particles were added to the solution, and then the mixture was stirred at 60°C for 24 hours. After the reaction, the generated solid particles were separated by centrifugation and dried to obtain ZIF-8@ZIF-67 precursor particles.
[0029] (2) Synthesis of Co3O4-CNT: 0.5 g ZIF-8@ZIF-67 precursor was heated to 800℃ in a tube furnace in an argon atmosphere at a heating rate of 2℃ / min and kept for 3 h to completely volatilize the zinc element; a black solid powder was obtained, which was acid-washed in 0.5 M sulfuric acid for 12 h to completely oxidize the Co element not wrapped in the carbon nanotubes, then centrifuged and washed with deionized water, and dried at 60℃. The dried powder was heated to 350℃ in an air atmosphere in a tube furnace at a heating rate of 2℃ / min for oxidation and kept for 4 h to obtain the microcage-anchored carbon nanotube Co3O4-CNT monomer material.
[0030] (3) Synthesis of Ti3C2T x @Co3O4-CNT composite material: Using MOF derivative Co3O4-CNT monomer material and Ti3C2T x Simply mix and stir. First, take 80 mg Co3O4-CNT and disperse it in 30 mL deionized water. Then slowly add 25 mL of a small layer containing 40 mg Ti3C2T x The colloidal solution was stirred for 30 minutes. Then it was transferred to a vacuum freeze dryer and dried at 1 Pa atmospheric pressure and -45 °C for 48 h to obtain a composite material Ti3C2T with a layer of micro-cage-anchored carbon nanotubes on the surface of the flake titanium carbide. x @Co3O4-CNT.
[0031] Step 2, Ti3C2T xPreparation of @Co3O4-CNT electrode: 80% by weight of active material, 10% by weight of conductive carbon black, and 10% by weight of PVDF binder were mixed with an appropriate amount of NMP, coated on copper foil, vacuum dried at 80 °C overnight, and then cut into discs with a diameter of 1.6 cm to keep the loading capacity of active material at 1 mg / cm 2 , electrolyte 1.0 M LiPF6 as solution. Lithium ion capacitor LIC (<0.01 ppm oxygen and water) was assembled in an argon-filled glove box, AC as the positive electrode, glass fiber Whatman GF / D as the separator, and 1.0 MLiPF6 electrolyte dissolved in EC:DEC=1:1 Vol%.
[0032] Example 3 Step 1, Ti3C2T x Preparation of @Co3O4-CNT: (1) Synthesis of ZIF-8@ZIF-67 precursor particles: 1) Preparation of ZIF-8 particles: Weigh 5.8 g of zinc nitrate hexahydrate and 6.4 g of 2-methylimidazole respectively and dissolve them in 150 mL of methanol. Then, stir the mixture at 60°C for 24 hours. After the reaction, separate the generated solid particles from the solution by centrifugation and dry them. After the above steps, ZIF-8 particles can be obtained.
[0033] 2) Preparation of ZIF-8@ZIF-67 precursor particles: 5.82 g of cobalt nitrate hexahydrate and 6.16 g of 2-methylimidazole were weighed separately and dissolved in 100 mL of methanol. 0.5 g of the prepared ZIF-8 particles were added to the solution, and then the mixture was stirred at 60°C for 24 hours. After the reaction, the generated solid particles were separated by centrifugation and dried to obtain ZIF-8@ZIF-67 precursor particles.
[0034] (2) Synthesis of Co3O4-CNT: 0.5 g ZIF-8@ZIF-67 precursor was heated to 800℃ in a tube furnace in an argon atmosphere at a heating rate of 2℃ / min and kept for 3 h to completely volatilize the zinc element; a black solid powder was obtained, which was acid-washed in 0.5 M sulfuric acid for 12 h to completely oxidize the Co element not wrapped in the carbon nanotubes, then centrifuged and washed with deionized water, and dried at 60℃. The dried powder was heated to 350℃ in an air atmosphere in a tube furnace at a heating rate of 2℃ / min for oxidation and kept for 4 h to obtain the microcage-anchored carbon nanotube Co3O4-CNT monomer material.
[0035] (3) Synthesis of Ti3C2T x @Co3O4-CNT composite material: Using MOF derivative Co3O4-CNT monomer material and Ti3C2T x Simple blending and stirring, first take 120 mg Co3O4-CNT dispersed in 30 mL deionized water, slowly add 25 mL of a small layer of 40 mg Ti3C2 colloidal solution and stir for 30 minutes. Then transfer to a vacuum freeze dryer and dry at 1 Pa atmospheric pressure and -45 ° C for 48 h to obtain a composite material Ti3C2T with a layer of micro-cage-anchored carbon nanotubes on the surface of the sheet-like titanium carbide. x @Co3O4-CNT.
[0036] Step 2, Ti3C2T x Preparation of @Co3O4-CNT electrode: 80% by weight of active material, 10% by weight of conductive carbon black, and 10% by weight of PVDF binder were mixed with an appropriate amount of NMP, coated on copper foil, vacuum dried at 80 °C overnight, and then cut into discs with a diameter of 1.6 cm to keep the loading capacity of active material at 1 mg / cm 2 , electrolyte 1.0 M LiPF6 as solution. Lithium ion capacitor LIC (<0.01 ppm oxygen and water) was assembled in an argon-filled glove box, AC as the positive electrode, glass fiber Whatman GF / D as the separator, and 1.0 MLiPF6 electrolyte dissolved in EC: DEC=1:1 Vol%.
[0037] Example 4 Step 1, Ti3C2T x Preparation of @Co3O4-CNT: (1) Synthesis of ZIF-8@ZIF-67 precursor particles: 1) Preparation of ZIF-8 particles: Weigh 5.8 g of zinc nitrate hexahydrate and 6.4 g of 2-methylimidazole respectively and dissolve them in 150 mL of methanol. Then, stir the mixture at 60°C for 24 hours. After the reaction, separate the generated solid particles from the solution by centrifugation and dry them. After the above steps, ZIF-8 particles can be obtained.
[0038] 2) Preparation of ZIF-8@ZIF-67 precursor particles: 5.82 g of cobalt nitrate hexahydrate and 6.16 g of 2-methylimidazole were weighed separately and dissolved in 100 mL of methanol. 0.75 g of the prepared ZIF-8 particles were added to the solution, and then the mixture was stirred at 60°C for 24 hours. After the reaction, the generated solid particles were separated by centrifugation and dried to obtain ZIF-8@ZIF-67 precursor particles.
[0039] (2) Synthesis of Co3O4-CNT: 0.5 g ZIF-8@ZIF-67 precursor was heated to 850℃ in a tube furnace in an argon atmosphere at a heating rate of 3℃ / min for 3 h, so that the zinc element was completely volatilized; a black solid powder was obtained, which was acid-washed in 0.5 M sulfuric acid for 12 h to completely oxidize the Co element not wrapped in the carbon nanotubes, then centrifuged and washed with deionized water, and dried at 60℃. The dried powder was heated to 400℃ in an air atmosphere in a tube furnace at a heating rate of 3℃ / min for oxidation and kept for 4 h to obtain the microcage-anchored carbon nanotube Co3O4-CNT monomer material.
[0040] (3) Synthesis of Ti3C2T x @Co3O4-CNT composite material: Using MOF derivative Co3O4-CNT monomer material and Ti3C2T x Simply mix and stir. First, take 120 mg Co3O4-CNT and disperse it in 30 mL deionized water. Then slowly add 25 mL of a small layer containing 40 mg Ti3C2T x The colloidal solution was stirred for 30 minutes. Then it was transferred to a vacuum freeze dryer and dried at 1 Pa atmospheric pressure and -45 °C for 48 h to obtain a composite material Ti3C2T with a layer of micro-cage-anchored carbon nanotubes on the surface of the flake titanium carbide. x @Co3O4-CNT.
[0041] Step 2, Ti3C2T x Preparation of @Co3O4-CNT electrode: 80% by weight of active material, 10% by weight of conductive carbon black, and 10% by weight of PVDF binder were mixed with an appropriate amount of NMP, coated on copper foil, vacuum dried at 80 °C overnight, and then cut into discs with a diameter of 1.6 cm to keep the loading capacity of active material at 1 mg / cm 2 , electrolyte 1.0 M LiPF6 as solution. Lithium ion capacitor LIC (<0.01 ppm oxygen and water) was assembled in an argon-filled glove box, AC as the positive electrode, glass fiber Whatman GF / D as the separator, and 1.0 MLiPF6 electrolyte dissolved in EC: DEC=1:1 Vol%.
[0042] Example 5 Step 1, Ti3C2T x Preparation of @Co3O4-CNT: (1) Synthesis of ZIF-8@ZIF-67 precursor particles: 1) Preparation of ZIF-8 particles: Weigh 5.8 g of zinc nitrate hexahydrate and 6.4 g of 2-methylimidazole respectively and dissolve them in 150 mL of methanol. Then, stir the mixture at 60°C for 24 hours. After the reaction, separate the generated solid particles from the solution by centrifugation and dry them. After the above steps, ZIF-8 particles can be obtained.
[0043] 2) To prepare ZIF-8@ZIF-67 precursor particles, 5.82 g of cobalt nitrate hexahydrate and 6.16 g of 2-methylimidazole were weighed and dissolved in 100 mL of methanol. 0.75 g of the prepared ZIF-8 particles were added to the solution, and then the mixture was stirred at 60°C for 24 hours. After the reaction, the generated solid particles were separated by centrifugation and dried to obtain ZIF-8@ZIF-67 precursor particles.
[0044] (2) Synthesis of Co3O4-CNT: 0.5 g ZIF-8@ZIF-67 precursor was heated to 850℃ in a tube furnace in an argon atmosphere at a heating rate of 4℃ / min for 3 h, so that the zinc element was completely volatilized; a black solid powder was obtained, which was acid-washed in 0.5 M sulfuric acid for 12 h to completely oxidize the Co element not wrapped in the carbon nanotubes, then centrifuged and washed with deionized water, and dried at 60℃. The dried powder was heated to 400℃ in an air atmosphere in a tube furnace at a heating rate of 4℃ / min for oxidation and kept for 4 h to obtain the microcage-anchored carbon nanotube Co3O4-CNT monomer material.
[0045] (3) Synthesis of Ti3C2T x @Co3O4-CNT composite material: Using MOF derivative Co3O4-CNT monomer material and Ti3C2T x Simply mix and stir. First, take 160 mg Co3O4-CNT and disperse it in 30 mL deionized water. Then slowly add 25 mL of a small layer containing 40 mg Ti3C2T x The colloidal solution was stirred for 30 minutes. Then it was transferred to a vacuum freeze dryer and dried at 1 Pa atmospheric pressure and -45 °C for 48 h to obtain a composite material Ti3C2T with a layer of micro-cage-anchored carbon nanotubes on the surface of the flake titanium carbide. x @Co3O4-CNT.
[0046] Step 2, Ti3C2T x Preparation and electrochemical performance test of @Co3O4-CNT electrode: 80% by weight of active material, 10% by weight of conductive carbon black, and 10% by weight of PVDF binder were mixed with an appropriate amount of NMP, coated on copper foil, vacuum dried at 80 °C overnight, and then cut into discs with a diameter of 1.6 cm to keep the loading capacity of active material at 1 mg / cm 2 , electrolyte 1.0 M LiPF6 as solution. Lithium ion capacitor LIC (<0.01 ppm oxygen and water) was assembled in an argon-filled glove box, AC as the positive electrode, glass fiber Whatman GF / D as the separator, and 1.0 MLiPF6 electrolyte dissolved in EC: DEC=1:1 Vol%.
[0047] Test Case Phase characterization was carried out using X-ray diffraction analysis (SEM), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS).
[0048] A three-electrode system was used, with Co3O4-CNT monomer material and Ti3C2T x @Co3O4-CNT composite material was used as the working electrode, platinum sheet as the counter electrode, (Hg / HgO) as the reference electrode, and Ti3C2T was tested using Shanghai Chenhua CHI660E electrochemical workstation in 3M KOH electrolyte. x @Electrochemical properties of Co3O4-CNT electrodes, such as cyclic voltammetry, constant current charge and discharge, AC impedance and cycle stability tests.
[0049] (1) Electrochemical performance test of the electrode sheet prepared in Example 1 of the present invention: Reference Figure 3, is the Ti3C2T prepared in Example 1 x XRD pattern of @Co3O4-CNT-1 composite material ( Figure 3 (a)). The tested Ti3C2T x The peak positions of the X-ray diffraction peaks of the @Co3O4-CNT-1 composite material are basically consistent with the peak positions of the PDF card of Co3O4. The peaks of 19.0, 31.3, 36.9, 44.8, 59.4 and 65.3 correspond to the (111), (220), (311), (400), (511), (440) planes of Co3O4 respectively (JCPDS No.76-1802). The XRD spectrum of the composite material contains Ti3C2T x , Co3O4, and no impurity phase. These results further confirm that Ti3C2T x Successful preparation of @Co3O4-CNT-1.
[0050] (2) Electrochemical performance test of the electrode sheet prepared in Example 2 of the present invention: Reference Figure 3 , is the Ti3C2T prepared in Example 2 x XRD pattern of @Co3O4-CNT-2 composite material ( Figure 3 (a)). The tested Ti3C2T x The peak positions of the X-ray diffraction peaks of the @Co3O4-CNT-2 composite material are basically consistent with the peak positions of the PDF card of Co3O4. The peaks of 19.0, 31.3, 36.9, 44.8, 59.4 and 65.3 correspond to the (111), (220), (311), (400), (511), (440) planes of Co3O4 respectively (JCPDS No.76-1802). The XRD spectrum of the composite material contains Ti3C2T x , Co3O4, and no impurity phase. These results further confirm that Ti3C2T x Successful preparation of @Co3O4-CNT-2.
[0051] (3) Electrochemical performance test of the electrode sheet prepared in Example 3 of the present invention: Reference Figure 1 , is the Co3O4-CNT monomer material prepared in Example 3 ( Figure 1 a. Figure 1 b) Ti3C2T x @Co3O4-CNT ( Figure 1d) Microscopic morphology of the composite material. It can be seen that the prepared Co3O4-CNT monomer material has a clear dodecahedral shape, which is very regular in shape, with a side length of about 5 microns, and is concentrated, and there are fine fibers distributed on the surface. Ti3C2T x The polyhedral and layered structures of @Co3O4-CNT composites are well preserved, which further suppresses the x The accumulation of nanosheets indicates that the composite of the two is relatively successful, and the particle size of the material is relatively uniform, maintained at about 5 microns.
[0052] Reference Figure 2 , is the Co3O4-CNT monomer material prepared in Example 3 ( Figure 2 b. Figure 2 c. Figure 2 e) TEM image of Ti3C2T x @Co3O4-CNT composite material( Figure 2 d) TEM image. Figure 2 It can be seen that there is a large amount of titanium carbide distributed around the Co3O4-CNT monomer material, and after the composite, the Co3O4-CNT monomer material still maintains its original relatively regular shape without being destroyed; Ti3C2T x It is connected to the Co3O4-CNT monomer material with a network structure, and the composite of the two is relatively successful.
[0053] Reference Figure 3 , Co3O4-CNT monomer material and Ti3C2T prepared in Example 3 x XRD patterns of @Co3O4-CNT composite materials ( Figure 3 (b)). The tested Co3O4 materials and Ti3C2T x The peak positions of the X-ray diffraction peaks of the @Co3O4-CNT composite material are basically consistent with the peak positions of the PDF card of Co3O4. The peaks of 19.0, 31.3, 36.9, 44.8, 59.4 and 65.3 correspond to the (111), (220), (311), (400), (511), and (440) planes of Co3O4, respectively (JCPDS No.76-1802). The XRD spectrum of the composite material contains the characteristic peaks of Ti3C2 and Co3O4, and there is no impurity phase. These results also further confirm that Ti3C2T x Successful preparation of @Co3O4-CNT.
[0054] Reference Figure 4 , is the Ti3C2T prepared in Example 3 x@X-ray photoelectron spectroscopy (XPS) of Co3O4-CNT composites. The wide scan XPS spectrum shows the binding energies of Ti 2p, Co 2p, N 1s, c1s, and o1s, indicating that Ti3C2T x @Co3O4-CNT composite material was successfully prepared.
[0055] Reference Figure 5 , Co3O4-CNT monomer material and Ti3C2T prepared in Example 3 x @CV graph of Co3O4-CNT composite material at different scan rates in a three-electrode system. By calculating the specific capacitance of the material, taking 2 mv / s as an example, the specific capacitance of Co3O4-CNT monomer material is 761 F / g, and that of Ti3C2T x @The specific capacitance of the Co3O4-CNT composite material is 984 F / g. The specific capacitance of the composite material increases, indicating that the composite material has better electrochemical properties.
[0056] Reference Figure 6 , Co3O4-CNT monomer material and Ti3C2T prepared in Example 3 x @GCD curves of Co3O4-CNT composite materials at different current densities in a three-electrode system. Taking 0.5 A / g as an example, the specific capacitance of Co3O4-CNT monomer material is 749F / g, and Ti3C2T x The @Co3O4-CNT composite material shows an excellent specific capacitance of 974 F / g, indicating that the composite material has better charge and discharge efficiency. After compounding, the specific capacitance of the material is significantly improved. At a high current density of 2A / g, the GCD curve of the composite material can still maintain a good triangular symmetric shape, and the specific capacitance value is still as high as 900 F / g, showing good rate performance.
[0057] Reference Figure 7 , is the Ti3C2T prepared in Example 3 x @Cycling performance of Co3O4-CNT composites. Testing at 2 A / g current density for 3000 cycles showed that the composite can maintain 89% of its initial capacitance. Ti3C2T x @Co3O4-CNT composites are viable options for electrode materials in high-performance lithium-ion capacitors.
[0058] Reference Figure 8 , which are CV graphs of the lithium ion capacitor assembled in Example 3 at different scan rates. It can be seen from the figure that the capacitor has a stronger current response, a more positive reduction potential and a more negative oxidation potential on the CV curve, and a higher peak current, indicating that the latter Li + Conversion is easier to do.
[0059] Reference Fig. 9 , which is the GCD diagram of the lithium ion capacitor assembled in Example 3. It can be seen from the figure that the assembled capacitor has a very high charge and discharge efficiency. By calculating its specific capacitance, it is found that it has an excellent specific capacitance of 160F / g at 2A / g. This also shows that the prepared electrode material has relatively excellent electrochemical properties and can meet the energy storage requirements of supercapacitors.
[0060] Reference Fig.10 , which is the EIS graph of the lithium ion capacitor assembled in Example 3. The EIS image of the assembled capacitor shows that the internal resistance Rs of the capacitor system is 8.89Ω, and its charge transfer resistance Rct is also 69.15Ω.
[0061] Reference Fig.11 , which is the cycle performance of the lithium ion capacitor assembled in Example 3. The test of the assembled capacitor for 3000 cycles at a current density of 2 A / g shows that the composition can maintain 92% of the initial capacitance, indicating that it has relatively excellent electrochemical performance.
[0062] (4) Electrochemical performance test of the electrode sheet prepared in Example 4 of the present invention: Reference Figure 3 , is the Ti3C2T prepared in Example 4 x XRD pattern of @Co3O4-CNT-4 composite material ( Figure 3 (a)). The tested Ti3C2T x The peak positions of the X-ray diffraction peaks of the @Co3O4-CNT-4 composite material are basically consistent with the peak positions of the PDF card of Co3O4. The peaks of 19.0, 31.3, 36.9, 44.8, 59.4 and 65.3 correspond to the (111), (220), (311), (400), (511), (440) planes of Co3O4 respectively (JCPDS No.76-1802). The XRD spectrum of the composite material contains Ti3C2T x , Co3O4, and no impurity phase. These results further confirm that Ti3C2T x Successful preparation of @Co3O4-CNT-4.
[0063] (5) Electrochemical performance test of the electrode sheet prepared in Example 5 of the present invention: Reference Figure 3 , is the Ti3C2T prepared in Example 5 x XRD pattern of @Co3O4-CNT-5 composite material ( Figure 3 (a)). The tested Ti3C2T xThe peak positions of the X-ray diffraction peaks of the @Co3O4-CNT-5 composite material are basically consistent with the peak positions of the PDF card of Co3O4. The peaks of 19.0, 31.3, 36.9, 44.8, 59.4 and 65.3 correspond to the (111), (220), (311), (400), (511), (440) planes of Co3O4 respectively (JCPDS No.76-1802). The XRD spectrum of the composite material contains Ti3C2T x , Co3O4, and no impurity phase. These results further confirm that Ti3C2T x Successful preparation of @Co3O4-CNT-5.
[0064] From the above test examples, it can be seen that the Ti3C2T prepared in the embodiment of the present invention x The Co3O4-CNT electrode exhibited good electrochemical performance. At a current density of 0.5 A / g, the specific capacitance of the prepared Co3O4-CNT monomer material was 749 F / g, and the specific capacitance of the Ti3C2T x The Co3O4-CNT composite material has an excellent specific capacitance of 974 F / g, indicating that the composite material has better charge and discharge efficiency. After compounding, the specific capacitance of the material is significantly improved. x @Co3O4-CNT composite material can still maintain a good triangular symmetrical shape at a high current density of 2A / g, and the specific capacitance value is still as high as 900 F / g, showing good rate performance. In addition, Ti3C2T x @Co3O4-CNT composite material exhibits excellent stability. Under the condition of current density of 2A / g, the capacity still has 89% of the original capacity after 3000 cycles of constant current charge and discharge.
[0065] Since the prepared Ti3C2T x @Co3O4-CNT composite material has excellent electrochemical properties, so it is used as the negative electrode, AC as the positive electrode, glass fiber Whatman GF / D as the separator, and 1.0 M LiPF6 electrolyte to assemble a lithium ion capacitor and test it on Shanghai Chenhua CHI660E electrochemical workstation. The assembled lithium ion capacitor was tested for 3000 cycles at a current density of 2 A / g, showing that the combination can maintain 92% of the initial capacitance. This shows that it has relatively excellent electrochemical properties and is expected to create an environmentally friendly high-performance energy storage device that can achieve rapid energy conversion and storage, meet the energy needs of human production and life, save traditional energy use, and reduce pollution.
[0066] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A two-dimensional titanium carbide multi-level composite material modified by micro-cage anchored carbon nanotubes, characterized in that: Co3O4-CNT loaded on Ti3C2T x The surface of the Co3O4 is a hollow dodecahedral microcage structure, the CNT is attached to the outer surface of the Co3O4 hollow dodecahedral microcage structure, and the CNT is anchored by the Co3O4 on the outer surface of the microcage.
2. A method for preparing the two-dimensional titanium carbide multi-level composite material modified by microcage-anchored carbon nanotubes according to claim 1, characterized in that: The following steps are involved: Step 1, dissolving zinc nitrate hexahydrate and 2-methylimidazole in methanol, heating and keeping the mixture warm, stirring, separating and drying solid particles generated by the reaction, and obtaining ZIF-8 precursor particles; Step 2, dissolving cobalt nitrate hexahydrate and 2-methylimidazole in methanol to form a mixed solution, then adding the ZIF-8 precursor particles prepared in step 1 to the mixed solution, heating and heat preservation, stirring, separating and drying the solid particles generated by the reaction, and obtaining ZIF-8@ZIF-67 precursor particles; Step 3, taking ZIF-8@ZIF-67 precursor particles, calcining to volatilize the zinc element in the inner layer ZIF-8 and grow carbon nanotubes on the surface of the outer layer ZIF-67, then acid washing, washing, drying, and then oxidizing to obtain Co3O4-CNT monomer material; Step 4: Take Co3O4-CNT monomer material and Ti3C2T x The nanopowder colloidal suspension was mixed in deionized water to form a colloid and stirred, and then freeze-dried to obtain Ti3C2T x @Co3O4-CNT multi-level composite material, that is, the two-dimensional nano-titanium carbide multi-level composite material modified by the micron cage anchored carbon nanotubes.
3. The method for preparing the two-dimensional titanium carbide multi-level composite material modified by microcage-anchored carbon nanotubes according to claim 2, characterized in that: The mass ratio of zinc nitrate hexahydrate to 2-methylimidazole in step 1 is (5.7~5.9): (6.3~6.5).
4. The method for preparing the two-dimensional titanium carbide multi-level composite material modified by microcage-anchored carbon nanotubes according to claim 2, characterized in that: In step 1, the reaction system is heated to 55-65° C. and stirred for 22-26 h.
5. The method for preparing the two-dimensional titanium carbide multi-level composite material modified by microcage-anchored carbon nanotubes according to claim 3, characterized in that: In step 2, the mass ratio of cobalt nitrate hexahydrate, 2-methylimidazole and ZIF-8 precursor particles is (5.7-5.9): (6.0-6.2): (0.25-0.75); the reaction system is heated to 55-65° C. and stirred for 22-26 hours.
6. The method for preparing the two-dimensional titanium carbide multi-level composite material modified by microcage-anchored carbon nanotubes according to claim 3, characterized in that: In step 3, the ZIF-8@ZIF-67 precursor particles are placed in a protective atmosphere for calcination, and are heated to 750~850℃ at a heating rate of 2~4℃ / min and calcined for 2.5~3.5h.
7. The method for preparing the two-dimensional titanium carbide multi-level composite material modified by microcage-anchored carbon nanotubes according to claim 3, characterized in that: Step 3: Heat to 300-400°C for oxidation at a heating rate of 2-4°C / min in an air atmosphere and keep warm for 3.5-4.5 h.
8. The method for preparing the two-dimensional titanium carbide multi-level composite material modified by microcage-anchored carbon nanotubes according to claim 3, characterized in that: In step 4, Co3O4-CNT monomer material, Ti3C2T x The dosage ratio of nano powder colloid and deionized water is (80~160)g: 25L: 30L.
9. The method for preparing the two-dimensional titanium carbide multi-level composite material modified by microcage-anchored carbon nanotubes according to claim 8, characterized in that: Step 4 Ti3C2T x The concentration of nano powder colloid is 1.6 g / L.
10. Use of the microcage-anchored carbon nanotube-modified two-dimensional titanium carbide multi-level composite material according to claim 1 as an electrode material.
Citation Information
Patent Citations
Preparation method of Ti3AlC2 ceramic powder
CN103601498A
Preparation method of granular titanium dioxide / two-dimensional nano-titanium carbide composite material
CN104495918B